Penerapan Model Servqual sebagai Media untuk Menilai Kualitas Pelayanan di Bank NTT - Nazarudin, Hamzah; Lao, Hans Arisandi; Attubel, May Munah; Sayd, Anastasia Imelda (Jurnal Ilmiah Aset, 2017)
Servqual model is a populer model of banking sevice and until now is used as a reference in marketing research. Servqual is an instrument to asses the service qualitry developed by Parasurahman, Zethamil, and berry in a series of their research to the service sector. This model is olso known as Gap Model or discrepancy between the customer expectation and reality (performance) of the received service this model is closely related with the customer satisfacton. In servqual model, the service quality is defined as the assestment or global attitude regarding the superiority of a service (Parasuraman, et al, 1985) All parties who buy and consume the banking service will give different assesment to the service quality, it is because of the banking service has the everchanging characteristic, Furthermore, Parasurahman et al (1993) found that the principal dimensions that define the servqual model are as follow (1) Physical evidence that is the appearance and physical facilities, transaction equipment and comunication media. (2) Reliability is the ability to provide the promise service immediately or timely, accurate and satisfaction. (3) Responsiveness is the willingness of the service provider to help customers and provide service responsively. (4) Assurance is the guarantees given to the cistomers include the willingness, courtesy and the trustworthy attitude of the employees. (5) Empathy is the concern of service providers in the form of attention to the needs and desires of customers.